2018
DOI: 10.1002/tee.22798
|View full text |Cite
|
Sign up to set email alerts
|

A new model approach of electrical cyber physical systems considering cyber security

Abstract: The integration of modern computing and advanced communication technologies with power grids has led to the emergence of electrical cyber physical systems (ECPSs). However, with the massive applications of communication technologies, power grids are becoming more vulnerable to cyber attacks, and there is no general model for analyzing the influence of such attacks. This paper focuses on modeling ECPSs considering cyber security. A multiple characteristic association (MCA) approach is proposed for analyzing cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our analysis revealed that in the last decade, CPSs have emerged as a new paradigm and as a result of the increased growth, complexity and heterogeneity of these infrastructures [14,82], the volume and the variety of vulnerabilities and attacks have evolved highlighting the need for defence mechanisms [147], need for cyber resilience and capability to support DFIR [26,29,30,33]. In this paper, the analysis of the primary studies supports our assertion that CPS-related cyber resilience and DFIR are active research domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis revealed that in the last decade, CPSs have emerged as a new paradigm and as a result of the increased growth, complexity and heterogeneity of these infrastructures [14,82], the volume and the variety of vulnerabilities and attacks have evolved highlighting the need for defence mechanisms [147], need for cyber resilience and capability to support DFIR [26,29,30,33]. In this paper, the analysis of the primary studies supports our assertion that CPS-related cyber resilience and DFIR are active research domains.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of cybercrime has been greatly facilitated by the proliferation of modern advanced electronic communication technologies and the integration of IoT with physical systems [17,28,33]. High profile cyberattacks on ICSs have been well reported for some years, such as the Stuxnet malware targeting the Iranian nuclear plant [34], the attack on the Ukrainian power grid [35] or Norsk Hydro, a renewable energy supplier and the world's largest aluminium producer, which was compromised by the LockerGoga ransomware [32].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, significant efforts have been made to develop appropriate models to map out the interdependencies of complex systems. Even though several researchers attempted to model dependencies between all the critical infrastructures [ 28 , 29 , 30 ], the majority focused on limited numbers of critical infrastructures [ 31 , 32 ], particularly on the power and ICT infrastructures [ 33 , 34 ].…”
Section: Related Workmentioning
confidence: 99%
“…An empirical study on different CIs showed that energy and telecommunications are the main cascading-initiating sectors [ 23 ]. As a result, significant efforts have been made in the last few years to study and model the interdependencies of power systems combined with ICT systems, viewed as complex cyber-physical systems, to improve defensive and protective strategies in the cyber and physical layers of power systems [ 33 , 34 , 35 , 36 , 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…Authors 18 have described the effects of cascading failures and cyber-attacks in the electrical cyber physical systems. Modeling of false data injection attack (FDIA) and their effects on the power system is studied in the literature.…”
mentioning
confidence: 99%